FROMULATION AND EVALUATION OF ANTICANCER CAPSULE FROM BANANA LEAVES. - Londhe Gayatri Sudhakar,; Dube Tanuja Goraksha,; Waghachaure Ravina Vilas,; Kolekar Sunil Narsing,; Punekar Rushikesh Rohidas,; Pansare Vikram Jaysing,; Dr. Veer Sujata Umakant,; Dr. Khedkar Amol Navnath, (The Bioscan, 2026)
Banana leaves possess various bioactive phytoconstituents such as flavonoids, phenolic compounds, tannins, and antioxidants, which play an important role in scavenging free radicals and reducing oxidative stress. The present study aimed to formulate and evaluate antioxidant herbal capsules containing banana leaf extract Fresh banana leaves were collected, washed, shade dried, and powdered. The powdered material was extracted using a hydroalcoholic solvent by the maceration method. The obtained extract was concentrated and subjected to phytochemical screening and antioxidant evaluation. The dried extract was then formulated into hard gelatin capsules using suitable excipients including lactose, starch, and magnesium stearate. The prepared capsules were evaluated for various preformulation and post-formulation parameters such as bulk density, tapped density, angle of repose, Carr’s index, Hausner ratio, weight variation, disintegration time, moisture content, and dissolution study. The antioxidant study demonstrated significant free radical scavenging activity due to the presence of phenolic and flavonoid compounds. The formulated capsules showed satisfactory pharmaceutical properties with good flow characteristics, uniform weight variation, and acceptable disintegration time. The study concludes that banana leaf extract can be successfully formulated into antioxidant herbal capsules with promising antioxidant activity and acceptable evaluation parameters. These herbal capsules may serve as a natural antioxidant supplement for reducing oxidatistress and promoting overall health benefits.